Development and Characterization of Pharmaceutical Systems Containing Rifampicin - Antonella V. Dan Córdoba; Virginia Aiassa; Jesica A. Dimmer; Camila N. Barrionuevo; Mario A. Quevedo; Marcela R. Longhi; Ariana Zoppi (MDPI AG, 2023)
Rifampicin is a potent antimicrobial drug with some suboptimal properties, such as poor stability, low solubility, and variable bioavailability. Therefore, in the current study, a multicomponent complex between rifampicin, γ-cyclodextrin, and arginine was prepared with the aim of improving drug properties. Solubility was evaluated by phase-solubility studies. The mechanism of interaction was established through proton nuclear magnetic resonance spectroscopy and molecular modeling. Physicochemical characterization was investigated using Fourier transform-infrared spectroscopy, powder X-ray diffraction, and scanning electron microscopy. The dissolution properties, antimicrobial activity (antibacterial, antibiofilm, and antileishmanial), and stability of the different samples were studied. The results obtained in this investigation demonstrate that multicomponent complexes can improve the water solubility and dissolution rate of rifampicin, as well as its antibacterial and antileishmanial action, and present suitable stability. In conclusion, rifampicin complexed with γ-cyclodextrin and arginine is an attractive approach for developing pharmaceutical dosage forms of rifampicin with increased antimicrobial activities.